Identification and Characterization of an Arabidopsis thaliana Mutant lbt With High Tolerance to Boron Deficiency - Huai, Zexun; Peng, Lishun; Wang, Sheliang; Zhao, Hua; Shi, Lei; Xu, Fangsen (Frontiers in Plant Science, 2018)
Boron (B) is an essential micronutrient of plants. In the present study, we characterized an Arabidopsis mutant lbt with significant low-boron tolerance that was identified based on our previous mapping of QTL for B efficiency in Arabidopsis. Multiple nutrient-deficiency analyses point out that lbt mutant is insensitive to only B-limitation stress. Compared with wild-type Col-0, the fresh weight, leaf area, root length and root elongation rate of lbt mutant were significantly improved under B deficiency during vegetative growth. lbt mutant also showed the improvements in plant height, branches and inflorescences compared with Col-0 during the reproductive stage under B limitation. Ultrastructure analysis of the leaves showed that starch accumulation in lbt mutant was significantly diminished compared with Col-0. Furthermore, there were no significant differences in the expression of transporter-related genes and B concentrations between Col-0 and lbt mutant under both normal B and low-B conditions. These results suggest that lbt mutant has a lower B demand than Col-0. Genetic analysis suggests that the low-B tolerant phenotype of lbt mutant is under the control of a monogenic recessive gene. Based on the high-density SNP linkage genetic map, only one QTL for low-B tolerance was mapped on chromosome 4 between 10.4-14.8 Mb. No any reported B-relative genes exist in the QTL interval, suggesting that a gene with unknown function controls the tolerance of lbt to B limitation. Taken together, lbt is a low-B tolerant mutant that does not depend on the uptake or transport of B and is controlled by a monogenic recessive gene mapped on chromosome 4, and cloning and functional analysis of LBT gene are expected to reveal novel mechanisms for plant resistance to B deficiency.